2023
DOI: 10.1108/ijchm-01-2022-0036
|View full text |Cite
|
Sign up to set email alerts
|

The effect of employee recognition on restaurant employees’ job embeddedness, knowledge sharing and service orientation: abusive supervision as a moderator

Abstract: Purpose The purpose of this paper is to develop and test a research model that explores the interrelationships of employee recognition, job embeddedness (JE), knowledge sharing, service orientation and abusive supervision. Specifically, the model proposes that JE mediates the impact of recognition on knowledge sharing and service orientation, while abusive supervision moderates the indirect influence of recognition on knowledge sharing and service orientation via JE. The model also proposes that JE and knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 88 publications
0
24
0
Order By: Relevance
“…Future research should examine other potential mediating factors, such as team-level work engagement and job embeddedness (Ali Abadi et al. , 2023; Ampofo et al. , 2023), to explain various ways agile work practices influence team creativity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research should examine other potential mediating factors, such as team-level work engagement and job embeddedness (Ali Abadi et al. , 2023; Ampofo et al. , 2023), to explain various ways agile work practices influence team creativity.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the study investigated the mediating role of team efficacy in the relationship between agile work practices and team creativity. Future research should examine other potential mediating factors, such as team-level work engagement and job embeddedness (Ali Abadi et al, 2023;Ampofo et al, 2023), to explain various ways agile work practices influence team creativity. Lastly, this study was conducted in the context of the IT industry and emerging economy, limits generalizing its findings to other industries and economies.…”
Section: Limitations and Direction For Future Researchmentioning
confidence: 99%
“…Further, the study provided evidence of the mechanism through which agile work practices affect team performance. Therefore, future studies can explore other potential mediating variables, such as organizational commitment (Uraon and Gupta, 2021), work engagement (Ali Abadi et al, 2023), and job embeddedness (Ampofo et al, 2023), to understand the various ways in which agile work practices affect team performance.…”
Section: Limitations and Direction For Future Researchmentioning
confidence: 99%
“…In addition to exploring the consequences of abusive supervision, researchers have concluded that abusive supervision is an important boundary condition that weakens the positive effects of organizational resources (e.g. parental support, Xu et al , 2022; employee recognition, Ampofo et al , 2023), personal resource (e.g. resilience, Dai et al , 2019) and intensifies the negative effects of job demands (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%